Nutritional Qualities and Valorization Trends of Vegetable and Fruit Byproducts: A Comprehensive Review - Zenebe Tadesse Tsegay; Sarah Tewolde-Berhan Gebreegziabher; Guesh Mulaw (Journal of Food Quality)
Vegetable and fruit byproducts are different parts of vegetables and fruits plus secondary products derived from primary agrofood production processes. With the increasing growth of global vegetable and fruit production, utilization of their byproducts for recovery of health benefit dietary nutrients required emphasis. The current food system and manufacturers are inadequate to maximize the existing food or plant resources’ public demand concurrently to minimize environmental pollution. Important sources of nutritional qualities of these byproducts and their valorization trends are getting research interests. In this review, we have summarized the nutritional qualities and their means of valorization of vegetable and fruit byproducts which have maximum global production from the FAO (2021) published data. The nutritional qualities of the main byproducts are highlighted and the current trends to valorize them into innovative health-promoting products were assessed. Valorization investigations conducted on these byproducts into food additives (dietary fiber concentrates), nutraceuticals, edible food packaging materials, fermented beverages, and natural dyes were mainly focused on in this review. There are limitations in valorizing technologies of vegetable and fruit byproducts. Hence, further studies are vital to develop novel processing techniques for each of these byproducts. Benefiting from the food waste is a pearl of wisdom and ignoring the value can be participating in pollution.